81Kr Dating at the Guliya Ice Cap, Tibetan Plateau. Issue 12 (19th June 2019) - Tian, Lide; Ritterbusch, Florian; Gu, Ji‐Qiang; Hu, Shui‐Ming; Jiang, Wei; Lu, Zheng‐Tian; Wang, Di; Yang, Guo‐Min
Abstract: We present radiometric 81 Kr dating results for ice samples collected at the outlets of the Guliya ice cap in the western Kunlun Mountains of the Tibetan Plateau. This first application of 81 Kr dating on midlatitude glacier ice was made possible by recent advances in Atom Trap Trace Analysis, particularly a reduction in the required sample size down to 1 μL STP of krypton. Eight ice blocks were sampled from the bottom of the glacier at three different sites along the southern edges. The 81 Kr data yield upper age limits in the range of 15–74 ka (90% confidence level). This is an order of magnitude lower than the ages exceeding 500 ka which the previous 36 Cl data suggest for the bottom of the Guliya ice core. It is also significantly lower than the widely used chronology up to 110 ka established for the upper part of the core based on ice δ 18 O. Plain Language Summary: The oldest ice that has ever been found outside of the polar regions is from the bottom of the Guliya ice cap in the western Kunlun mountains on the Tibetan Plateau. Previous dating results from the Guliya ice core, drilled in 1992, indicate that the bottom ice is more than 500, 000 years old. However, due to the lack of alternative dating methods in that time range, the age scale of the Guliya ice core has so far not been checked independently. In this work we present dating results for the Guliya ice cap with a new dating method for ice based on the radioactive decay of the extremely rare krypton isotope 81 Kr. Eight ice samples were retrieved at three different margin sites of the Guliya ice cap, where the old bottom ice is expected to resurface. The 81 Kr measurements for these samples yield upper age limits in the range of 15–74 ka, which is significantly lower than the previous dating results for the ice core. Key Points: Radiometric 81 Kr dating of bottom ice from the Guliya ice cap is presented 81 Kr data yield upper age limits in the range of 15–74 ka 81 Kr results are difficult to reconcile with ages previously obtained for the Guliya ice core based on 36 Cl and δ 18 O